Effects of transport media and duration on the mortality and physiological responses in silver carp Hypophthalmichthys molitrix fingerlings (Dhaka University Journal of Biological Sciences, 2013)
This study evaluated the effects of three transport media i.e., well water (WW), pond water (PW) and mixture of the two (WPW; 1 : 1) and durations (1, 3, 6 and 9 hrs) on the mortality and physiological responses in silver carp, Hypophthalmichthys molitrix fingerlings in a transport simulation at 400 g/l loading density. While the total mortality was lower than 9% until 6 hrs of transport, it was very high (49 - 60%) at 9 hrs across all three treatment media. The highest level of cortisol was measured in the fingerlings simulated using WPW while the lowest level was detected in the fingerlings sampled form WW. The level of cortisol observed in the fingerlings simulated using PW was not different from other two media. Between durations, the levels of cortisol observed were significantly different. The highest chloride level was measured in the fingerlings simulated using WW while the lowest level was observed in the fingerlings sampled from WPW. PW did not result in different chloride level from those of WW and WPW. Among duration treatments, while 9 hrs resulted in the lowest level of chloride, the highest level was detected at 1 hr. The results suggest that WW, PW and WPW can be used as medium in transporting well conditioned silver carp fingerlings for 6 hrs with little mortality and less stress effects.Dhaka Univ. J. Biol. Sci. 22(1): 55-62, 2013 (January)